2012
DOI: 10.1093/ckj/sfs154
|View full text |Cite
|
Sign up to set email alerts
|

A single-centre comparison of the clinical outcomes at 6 months of renal transplant recipients administered Adoport®or Prograf®preparations of tacrolimus

Abstract: BackgroundThe use of generic formulations of immunosuppressive drugs in place of brand name drugs offers considerable cost savings. Brand name tacrolimus (Prograf®) came off patent in April 2008. However, published evidence supporting therapeutic equivalence of generic formulations of tacrolimus in solid organ transplantation is lacking. The South West Transplant Centre switched from administering Prograf® to a generic formulation (Adoport®) for de novo transplant recipients in November 2010. This study sought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…While no clear relationship between tacrolimus levels and the incidence of AKI could be determined in the adoport-treated recipients, the finding of statistically higher variability in dose/level ratio at day 14 does raise the possibility that adoport levels may have fluctuated enough to cause renal impairment. A similar finding was shown by Connor et al (16), who also demonstrated a non-significantly increased frequency of tacrolimus-related nephrotoxicity in adoport-treated renal transplant patients compared to historical controls treated with Prograf. However, at later time points, we were unable to either show variation in dose/level ratios or renal function suggesting that even if variation in the pharmacokinetics of Adoport predisposes to AKI in the early-phase post-LT, this is short lived and not associated with changes in long-term renal outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…While no clear relationship between tacrolimus levels and the incidence of AKI could be determined in the adoport-treated recipients, the finding of statistically higher variability in dose/level ratio at day 14 does raise the possibility that adoport levels may have fluctuated enough to cause renal impairment. A similar finding was shown by Connor et al (16), who also demonstrated a non-significantly increased frequency of tacrolimus-related nephrotoxicity in adoport-treated renal transplant patients compared to historical controls treated with Prograf. However, at later time points, we were unable to either show variation in dose/level ratios or renal function suggesting that even if variation in the pharmacokinetics of Adoport predisposes to AKI in the early-phase post-LT, this is short lived and not associated with changes in long-term renal outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…Similar patient and graft survival was reported in the selected studies. Graft loss was reported in two of the de novo studies after KT: in eight patients (15.7%) versus six patients (12.5 %) after generic and innovator Tac, respectively , and the Spartacus trial revealed 0% graft loss versus 2.6% (one patient) with generic and innovator Tac after KT, respectively . Furthermore, there were 2 (4.3%) versus no graft losses reported with de novo innovator Tac after LT .…”
Section: Resultsmentioning
confidence: 97%
“…In 2011, the tacrolimus produced by Sandoz under the name of Adoport â officially entered the market in Europe after being approved by the European Medicines Agency. Since then, many authors have performed clinical studies to test the efficacy and safety of Adoport â in different situations: conversion studies from Prograf â to Adoport â [16][17][18], as well as de novo use [19] and bioequivalence studies (postconversion) [20].…”
Section: Discussionmentioning
confidence: 99%